2008
DOI: 10.1302/0301-620x.90b8.20161
|View full text |Cite
|
Sign up to set email alerts
|

Embryology of the acetabular labral-chondral complex

Abstract: Damage to and repair of the acetabular labral-chondral complex are areas of clinical interest in the treatment of young adults with pain in the hip and in the prevention of degenerative arthritis of the hip. There are varying theories as to why most acetabular tears are located anterosuperiorly. We have studied the prenatal development of the human acetabular labral-chondral complex in 11 fetal hips, aged from eight weeks of gestation to term. There were consistent differences between the anterior and posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 22 publications
0
36
0
4
Order By: Relevance
“…The posterior region is directly attached to and continuous with the articular cartilage, and here the fibers are organized perpendicular to the margin. This histological difference may in part explain why most tears of the labrum are located anteriorly (Cashin et al 2008). …”
Section: Anatomy and Function Of The Labrummentioning
confidence: 99%
“…The posterior region is directly attached to and continuous with the articular cartilage, and here the fibers are organized perpendicular to the margin. This histological difference may in part explain why most tears of the labrum are located anteriorly (Cashin et al 2008). …”
Section: Anatomy and Function Of The Labrummentioning
confidence: 99%
“…1). The following soft-tissue and skeletal changes in DDH have also been reported in the clinical literature: acetabular labral tears (Fujii et al, 2009;Noguchi et al, 1999;Tanzer and Noiseux, 2004;Cashin et al, 2008;Tschauner and Hofman, 1998), degenerative changes to the acetabular rim (Ganz and Leunig, 2007;McCarthy and Lee, 2002;Fujii et al, 2009), abnormal femoral head and neck morphology and differences in limb length (Storer and Skaggs, 2006), valgus angulation at the knee (Kandemir et al, 2002), and osteoarthritis (OA) (Jacobsen et al, 2005;McCarthy and Lee, 2002;Haene et al, 2007;Jessel et al, 2009). Even if dysplasia and subluxation present as a unilateral condition, the contralateral hip joint will also be abnormal compared with a normal healthy hip, in terms of femoral neck anteversion, femoral neck-shaft angle, and increased acetabular anteversion (Jacobsen et al, 2006).…”
mentioning
confidence: 76%
“…[10] demonstrated that the anterior acetabular cartilage was covered by a hat-shaped anterior margin of the labrum cartilage complex, while the intra-articular projection of the labrum into the joint resulted in the formation of a crypt between the acetabular cartilage surface and the labrum. However, the posterior labrum was directly attached to the acetabular cartilage in the absence of an intra-articular projection.…”
Section: Discussionmentioning
confidence: 99%